We Need More Voices, Not Less! Promoting Employee Voice Through Transformational Leadership: The Mediating Role of Organization-Based Self-Esteem - Lopez-Bohle, S; Muñoz-Medina, L (SAGE Publications Ltd, 2025)
This study examines the empowering effect of transformational leadership on employees’ promotive voice behavior. In addition, the mediating effect of organization-based self-esteem and the moderating effect of job insecurity were investigated. Survey data were collected from 128 Chilean employees (enrolled in an executive business specialization program at a major Chilean university) three times using a time-lagged design. Latent moderated structural equation modeling was conducted to test the research hypotheses using Mplus. Results indicate that organization-based self-esteem fully mediates the positive relationship between transformational leadership and employees’ promotive voice behavior. Job insecurity had no significant moderating effect. This article contributes to the literature on transformational leadership by (1) providing insight into the role of organization-based self-esteem as a mechanism of follower transformation, (2) studying the boundary condition of quantitative job insecurity that may influence the effectiveness of transformational leadership, and (3) using a three-wave time-lagged design to understand these relationships. © The Author(s) 2025.